APLIKASI TUTORIAL INTERAKTIF PELAJARAN TEKNOLOGI INFORMASI & KOMUNIKASI SD CATURTUNGGAL III YOGYAKARTA - Harry Marthen Luther Hattu; Naniek Widyastuti; Mohammad Sholeh (Jurnal SCRIPT, 2015)
Subjects Information and Communication Technology is prepared to anticipate developments and the impact of technology, especially in information and communication in daily lives. Students who have attended, understand and practice the subjects of ICT by using a tutorial program is expected to have the capacity and confidence to understand the different types of information and communication technologies as well as the negative impacts and limitations, and able to use it to support the learning process and in life . This study is based on the identification of problems and needs of data on the SD Caturtunggal III Depok Sleman. The data collection using the method of observation, interviews and literature studies. The design of tutorial program using AutoPlay Media Studio software and other supporting devices. The studies have produced an interactive tutorial application program that has an attractive appearance and easy to use so that it can help students to not only understand but also guide students to immediately apply the material being studied. This interactive tutorial programs also facilitate teachers in elementary Single Chess III especially for subjects of ICT in presenting and managing the subject matter.